Universos fantásticos: os contos de Lygia Fagundes Telles - Silva, Wandeir Araújo da (2013)
This research intends to analyze the short-stories As formigas , O encontro , A mão no ombro A estrela branca e Lua crescente em Amsterdã , written by the brazilian author Lygia Fagundes Telles. We believe that the mentioned narratives can be used to evaluate the theories of the fantastic in this case, especially, the theory presented by the franco-bulgarian philosopher Tzevtan Todorov. Thus, we propose to observe how the fantastic is constructed, focusing on what we find in The fantastic: a structural approach to a literary genre. According to presented in this study, we believe that some Todorov s assertions about the fantastic can be reviewed. We inquire many structural factors presented in the definition of fantastic proposed by the theorist. As we can see in Telles short-stories, such a theory not always seems to include all the aesthetical resources used to create the fantastic. In the end of research, we also comment the social function of the genre, once that Todorov believes that the fantastic is attached only to the literary production found in the centuries XVIII and XIX. Telles short-stories show that contemporary writers continue to explore the themes of the fantastic however, they present new ways of composition.